The Mudejar Communities of the Kingdom of Castile in the 15th Century: A Review of the Current State of Research - Araus Ballesteros , Luis (En la España Medieval, 2025)
The last century of existence of the Mudejar communities is the best known by historians thanks to the greater abundance of documents. In this work, issues such as spatial distribution, institutions, society, culture and economy of the Muslims of the North of the Crown of Castile, are reviewed, pointing out their main characteristics.